Identifikasi Timbal dan Verifikasi Destruksi dengan Metode Spiking Pada Sampel Kangkung Darat Di Kota Pontianak - Virgilius Alleandro Tuah Talu; Hadi Kurniawan; Fajar Nugraha (Jurusan Farmasi Universitas Negeri Gorontalo, 2023)
Water spinach is a vegetable that is rich in benefits, apart from the benefits it has, it can also be a mediator for the spread of heavy metals to humans. One of the contaminants that can contaminate Water spinach is lead (Pb). Lead (Pb) is a pollutant that occurs in big cities and has toxic properties. Lead (Pb) contamination in water spinach can occur due to the influence of motor vehicle exhaust, waste, fertilizers and pesticides containing metals. Lead (Pb) contamination in vegetables such as Water spinach can have adverse effects on health such as poisoning and can cause various kinds of disorders such as digestive tract disorders. This study aims to identify lead (Pb) in Water spinach and find out whether the sample preparation method used is good and correct by using spiking method. The samples used in this study amounted to 5 samples spread at different market locations in Pontianak city using the technique purposive sampling. Water spinach samples were prepared using the wet destruction method, then qualitatively tested using 1N NaOH reagent. Method Spiking carried out by taking a standard solution of 1,000 ppm lead (Pb) as much as 1 ml and putting it into the sample to be prepared. The sample that has been prepared is then measured and the value is calculated %Recovery. The results of the qualitative test showed that after the sample was dripped using 1N NaOH reagent there was no white precipitate. The Result obtained in verification of destruction using the spiking method were concentration of 18.7515 ppm and a value %Recovery of 106.8833%. All samples of Water spinach that were tested qualitatively did not contain lead (Pb) and the preparation method used for analysis of ground kale was good and correct.